Reformulation of Dairy Cattle Concentrate Based on Rumen Degradable Protein to Undegradable Protein Ratio at Different Energy Levels: In Vitro Study. Issue 1 (1st April 2022) - Rosmalia, A; Dewi, N A; Permana, I G; Despal
Abstract: Asynchronous releasing rumen degradable protein (RDP) and energy reduces rumen microbial protein synthesis (MPS) and increases excess nutrients to the environment. Moreover, the ratio of RDP to rumen undegradable protein (RUP) was also important in improving the utilization of protein, especially for high-producing cows. However, the issue has not been a concern of most dairy concentrate manufacturers in tropical areas. The objective of this study was to determine the optimal ratio of RDP to RUP (RDUP) at different energy levels (TDN) of dairy cattle concentrate using in vitro method. The study used a 4 × 3 factorial randomized block design. The first factor was RDUP (1.50; 1.22; 1.00; 0.82) and the second factor was TDN levels (65%; 70%; 75%). Data were analyzed using ANOVA and followed by Duncan's test. RDUP and TDN treatments affected NH3 concentration without interaction. Total VFA concentration, rumen bacteria, and protozoa population did not affect by the treatments. Dry matter and organic matter digestibility increased with increasing RDUP and TDN levels with an average of 71.58% and 70.67%, respectively. It is concluded that dairy concentrate based on RDP:RUP ratio at 1.50 (60:40) and 75% TDN improves fermentability and in vitro digestibility.